4-amino-5-(trifluoromethyl)-4H-1, 2, 4-triazole-3-thiol as an effective corrosion inhibitor for low carbon steel in HCl environment: experimental and theoretical studies - Zehbah Ali Mohammed Al-Ahmed; Medhat M. Kamel; Mostafa A. A. Mahmoud; Sherin A. M. Ali; Ahmed Z. Ibrahim; Badria M. Alshehri (BMC Chemistry)
Abstract The compound 4-amino-5-(trifluoromethyl)-4H-1,2,4-triazole-3-thiol (ATFS) was assessed for its effectiveness in preventing corrosion of low-carbon steel (LCS) in a hydrochloric acid (HCl) solution with a concentration of 0.5 mol L−1. The inhibition performance of the ATFS compound was investigated by chemical, electrochemical, and quantum studies. The surface morphology of LCS was studied by scanning electron (SEM) and atomic force (AFM) microscopes. At 298 K, the inhibitory efficiency (IE) increased from 52.27 to 89% as the inhibitor concentration increased from 50 to 300 ppm. However, at 328 K and with 300 ppm of the ATFS compound, the IE decreased to 74.51%. The Tafel plot confirmed that the ATFS compound belonged to mixed-type inhibitors. An increase in inhibitor’s concentration resulted in an elevation of the activation energy of the corrosion process, indicating that the ATFS was physically adsorbed at the LCS surface. The adsorption followed the Langmuir’s isotherm. The ATFS decreased the capacitance of the double layer (Cdl) and increased the charge transfer resistance (Rct). The AFM results indicated that the average roughness of LCS in the HCl solution was 7.58 nm, which reduced to 4.79 nm in the presence of 300 ppm of the ATFS compound. The high IE of the ATFS inhibitor was verified by the quantum parameters that derived from the density functional theory (DFT). The low hardness value of ATFS compound (η = 0.095) suggested its high adsorbability onto the steel surface, however, the high global softness (σ = 10.482) indicated its strong capability as an inhibitor. Monte Carlo (MC) simulations demonstrated that the adsorption energy of ATFS at the LCS surface is significantly negative (− 287.12 kJ mol−1), indicating a strong interaction between the AFTS and LCS.